The impact of high-intensity exercise on patients with depression: a systematic review and meta-analysis of randomized controlled trials - Zeng, Junru; Wang, Hong (Frontiers in Public Health, 2025)
ObjectiveThis study systematically evaluated the effectiveness of high-intensity exercise as an intervention for patients with depression through meta-analysis.MethodsRelevant studies were retrieved from PubMed, Embase, Cochrane, and Web of Science up to June 30, 2025. Standardized mean differences (SMDs) with 95% confidence intervals (CIs) were calculated. Sensitivity and subgroup analyses were conducted to assess robustness and explore heterogeneity. Data analysis was performed using Review Manager 5.4.1 and Stata 15.1.ResultsNine randomized controlled trials (RCTs) with 514 participants were included (193 in the intervention group and 321 in the control group). Compared to controls, the intervention group showed greater improvement in depression severity, based on the Hamilton Rating Scale for Depression (HRSD) (SMD: –0.44; 95% CI: −0.69, −0.18; p = 0.0008) and overall depression scores (SMD: –0.23; 95% CI: −0.39, −0.07; p = 0.006). However, results from the Hamilton Depression Rating Scale (HAMD) (SMD: –0.17; 95% CI: −0.39, 0.06; p = 0.14) and Beck Depression Inventory (BDI-II) (SMD: 0.12; 95% CI: −0.10, 0.34; p = 0.28) were not significant. Similar outcomes were observed with Montgomery-Asberg Depression Rating Scale (MADRS), Patient Health Questionnaire Depression Scale (PHQ-9), and Geriatric Depression Scale (GDS) (SMD: –0.35; 95% CI: −0.70, 0.01; p = 0.06). No significant difference was found in Maximal Oxygen Uptake (VO2max) (SMD: 0.29; 95% CI: −0.22, 0.80; p = 0.27). Subgroup analysis revealed that long-term high-intensity exercise interventions were more effective than short-term ones. In patients with depression, those aged 60 years or older benefited more from high-intensity exercise compared to younger individuals aged 30–60 years. Among different exercise modalities, high-intensity aerobic exercise showed the greatest efficacy, followed by high-intensity resistance training, while high-intensity interval training was comparatively less effective.ConclusionCompared to the control group, high-intensity exercise modestly improves depressive symptoms in patients with depression. However, due to limitations such as small sample sizes, potential heterogeneity, and result instability, further validation through large-scale, multi-centre, randomized, double-blind clinical trials is warranted.